Factors that predict weight loss success differ by diet intervention type - Losavio, Jordan; Keenan, Michael J.; Gollub, Elizabeth A.; Silver, Heidi J. (Frontiers in Nutrition, 2023)
Background: Many types of diet intervention can achieve negative energy balance and successful weight loss in persons with obesity. However, within any dietary strategy, there is large inter-individual variation in the weight loss response. The aim of this study is to determine factors that predict weight loss success for diet interventions that vary by macronutrient and caloric composition. Methods: Participants with BMI 30.0 to 49.9 kg/m 2 self-selected one of three diet intervention trials for weight loss: low carbohydrate (LOW CHO), low fat (LOW FAT), or low calorie (LOW KCAL). Multivariable regression models were developed to determine the significance of predictor demographic, body composition, metabolic, clinical, and dietary variables for each diet type. Results: Weight loss over 12-16 weeks averaging -5.1 ± 4.0 kg from baseline weight, p < 0.001, was not significantly different among diet types. Several different factors were identified that account for the inter-individual variance in weight loss success. Regardless of diet type, the most robust predictor of weight loss success was completion of the intervention, accounting for 20-30% of the variance. Factors predicting diet intervention completion were age, physical activity level, blood leptin level, blood pressure, and the amount of weight loss occurring. Differences by diet type in cardiometabolic risk factor reduction were identified with LOW CHO decreasing glycemia/insulinemia factors, LOW FAT decreasing lipidemia factors, and LOW KCAL decreasing inflammatory factors. Conclusion: These data provide evidence to inform more precise and personalized approaches to diet intervention for weight loss and cardiometabolic health.